Identification and Characteristics of Multidrug-Resistant Ureaplasm urealyticum and Mycoplasma hominis Isolates among Female Patients with Recurrent Non-Gonococcal Urethritis in a Tertiary Hospital, China - Linlin Ma; Wei Chu; Xinyuan Feng; Peiyao Li; Binxian Li; Mingcheng Li (IMR Press, 2023)
Background: Concerns are increasing over the mechanisms of drug resistance pathogens among non-gonococcal urethritis (NGU) or cervicitis. The study aims to explore the distribution of Ureaplasm urealyticum (U. urealyticum) and Mycoplasma homins (M. homins) isolates, characteristics of multidrug resistance, and the underlying mechanism to allow clinicians to deliver rational therapy for NGU. Methods: Samples from cervical secretions of 246 patients with NGU were collected. Mycoplasma culture and drug susceptibility tests were performed, respectively. The resistance genes were detected by multiplex Polymerase Chain Reaction (PCR), and the PCR products were cloned and sequenced. Results: Out of 246 samples, the overall prevalence of U. urealyticum and/or M. hominis infection was 39.02% (96/246). In 96 culture positive samples, the overall infection rate of U. urealyticum was higher than that of the single M. hominis (46.87% vs. 28.13%) (p < 0.05), and the coinfection rate was 25.00% (24/96). Each U. urealyticum and M. hominis isolate exhibited resistance to at least three types of antimicrobial agents (manifest by more than 70% resistance to erythromycin, tetracycline, ciprofloxacin, and spiramycin, followed by ofloxacin, roxithromycin, azithromycin and josamycine (with resistance thereto of more than 50%)). More than 80% of U. urealyticum and M. hominis isolates were susceptible to minomycine and doxycycline, whereas 81.16% and 77.44% of both U. urealyticum and M. hominis isolates were also susceptible to minomycine and doxycycline. Surprisingly, the resistance rate of the mixed infection was higher that of erythromycin, tetracycline and ciprofloxacin comparison to the single infection (p < 0.05). All tetracycline-resistant isolates carried the tetM gene and 50% of erythromycin-resistant isolates carried the ermA gene. Conclusions: Among outpatients with recurrent NGU, the U. urealyticum infection dominated, followed by M. hominis, mixed U. urealyticum and M. hominis infection. Minomycine and doxycycline are recommended for empirical clinical treatment. The determination of U. urealyticum and M. hominis infection, antibiotic susceptibility testing is crucial for effective therapy.